A Comparative Study and Benchmarking on XML Parsers - Haw, Su Cheng; Rao, G. S. V. Radha Krishna (2007)
Due to its flexibility and efficiency in transmission of data, XML has become the emerging standard of data transfer and data exchange across the Internet. XML document must always be checked for well formedness before data transfer and exchange can take place. To choose the right parser for an organization respective system is crucial and critical; since improper parser will lead to degradation in performance and decrease in productivity. In this paper, we will do an extensive comparative study and benchmarking on the popular XML parsers found in the market today. In addition, we also propose a non-validating SAX based XML parser, xParse. We implemented our technique and present the performance results, which prove the viability of our approach.